Resolution of rare earth element interferences in fossil energy by-product samples using sector-field ICP-MS. (1st December 2016) - Thompson, Robert L.; Bank, Tracy; Roth, Elliot; Granite, Evan
Graphical abstract: Abstract: The supply and price of rare earth elements (REEs) have become a concern to many countries in the world, which has led to renewed interest in exploration and recovery of REEs from secondary or waste sources. Potential high REE waste sources that are of particular interest are coal mining, preparation, combustion, and other fossil energy by-products, including those from natural gas production. In this work, we have examined a set of five solid samples from the treatment of produced and flowback water containing elevated concentrations of barium. In order to confirm the correct concentrations of Eu, we studied these materials using sector field inductively coupled plasma mass spectrometry (SF-ICP-MS), which is capable of resolving species of nearly identical masses, including Eu and BaO. While the use of quadrupole inductively coupled plasma mass spectrometry (Q-ICP-MS) for the REE analysis of most geological sample matrices should pose no problem, the presence of large amounts of Ba, as encountered in water treatment solids from natural gas produced and flowback samples may require SF-ICP-MS for accurate determination of all REEs.